(untitled) (Itinera, 2024)
The article explores the philosophical implications of artificial intelligence (AI) in the realm of art, drawing from phenomenological perspectives. Firstly, it aims to clarify specific terms frequently used in philosophical and technological debates, thereby enhancing dialogue in the field and addressing underlying issues. The article focuses on questioning the role of art as an event of manifestation and explores the implications of AI on the relationship between art and Truth. In this regard, the analysis considers whether AI-generated art can truly engage in the ontological event as the human-created art, or if it merely remains a product of computational processes, lacking genuine existential depth. The goal is to return to the fundamental question of being of the artwork, seeking to understand how AI challenges or redefines traditional concepts of art’s essence.